Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Tahu Di Desa Air Teluk Kiri Kecamatan Teluk Dalam Kabupaten Asahan - Tari Fhon Na Arifin; Sugianto Sugianto; Siti Aisyah (Ecobuss, 2023)
The research conducted aims to analyze the internal and external factors of marketing strategies, analyze marketing strategies, and analyze which strategies are prioritized. This research was conducted at Ibu Iir's Tofu Factory located in Air Teluk Kiri Village, Teluk Dalam District, Asahan Regency, North Sumatra Province. The benefit of doing this research is that the company can find out the marketing strategy that will be carried out in the future, then apply the results of this research in the company. So that in the future the company is able to increase sales volume as desired. This research is a qualitative descriptive research. The data collection techniques used in this research are interviews, observations, document studies, and questionnaires. The results of the SWOT analysis, Mrs. Iir's Tofu Factory is in quadrant I position and the strategy used is Progressive. While the results of the QSPM matrix analysis the selected strategy is the Strenght-Opportunity strategy with a TAS result of 6.28.